Evaluate the effectiveness of ginger solution in reducing primary dysmenorrhea among nursing students - M, Poornima; H, Hemalatha (Indian Journal of Nursing Sciences, 2024)
The study was conducted to evaluate the effectiveness of ginger solution in reducing primary dysmenorrhea among nursing students and its significant association between the level of pain and demographic variables. Background: The onset of menstruation is a part of the biological maturation process. However, variability in menstrual cycle characteristics and menstrual disorders are common. It is estimated that about 50% of women experience some degree of dysmenorrhea with 10% of them incapacitated by it. About 40-70% of women aged 19-22 years suffer from dysmenorrhea and is associated with significant psychological, physical, behavioral and social factors. Materials and methods: The study design adopted was a true experimental approach (pretest-posttest control group design). Samples for the study were nursing students who had dysmenorrhea. Simple random sampling technique was used for selection of 50 samples and random allocation was adopted to assign 25 samples to experimental and 25 samples to control group. Results: The pretest data shows that in the experimental group, 5% (1) had a mild level of pain, majority 80% (20) of students had a moderate level of pain and 15%(4) had a severe level of pain and 0% had worst pain. Whereas in control group, 5% (1) had mild pain and the majority of nursing students 75 %( 19) had a moderate level of pain and 20 %( 5) had a severe level of pain. The post-test data shows that in the experimental group, the majority of nursing students 32% (8) had moderate, 40%(10) had a severe level of pain, 20%(2) had a very severe level of pain and8% (2) had worst level of pain. Whereas in control group, 48 %( 12) had moderate pain, 36 %( 9) had severe and 16% (4) had a very severe level of pains. Conclusion: Dysmenorrhea is the most common gynecologic disorder among female adolescents, with a prevalence of 60% to 93%. Dysmenorrhea was characterized by cramping lower abdominal pain that may radiate to the lower back and upper thighs and was commonly associated with nausea, head ache, fatigue, and diarrhea. The present study assessed the effectiveness of ginger solution on the reduction of pain during menstruation among nursing students. Based on statistical findings, it is evident that the ginger solution was effective in reducing the level of pain among nursing students.